Nature Interest: Comparison Between Students of Science-Related Study Programs and Non-Science-Related Study Programs at the Kerinci State Islamic Institute - Ananda, Feby; Sastria, Emayulia; Zebua, Dinyah Rizki Yanti (Journal of Science and Science Education, 2024)
Nature interest is an individual's interest in the natural environment, which includes curiosity, involvement, and enjoyment when in nature. This interest often leads to a drive to preserve nature and strengthen emotional connections with the natural world. This study aims to measure Nature Interest at the Kerinci State Islamic Institute. This study adapted the Nature Interest Scale instrument. This study used descriptive and comparative quantitative methods; the sample comprised 122 students. This study examined students' interest in nature and its impact on pro-environmental attitudes and behaviors. The results showed variations in interest between science and non-science students, influenced by educational background, academic orientation, and personal interests. Participation in nature-based solutions, such as ecosystem restoration and natural resource conservation, stimulates motivated motivation by encouraging involvement in pro-environmental practices. Environmental education has been shown to influence pro-environmental behavior, especially for science students who balance emotional and intellectual interests in nature. Emotional attachment to nature is the main motivational basis for nature protection behavior, although their science education does not always influence students' beliefs. Non-science students tended to be less interested in nature, but emotional connections to nature still influenced their pro-environmental attitudes and behaviors. Science students, especially biology, reported more positive attitudes, broader knowledge, and higher levels of nature-related activity than other majors and more pro-environmental attitudes than business majors. Environmental education increased environmental awareness, with environmental studies students showing higher awareness and greater appreciation for using the campus arboretum than students from other majors. Students’ environmental volunteerism values ​​varied by gender and stream of study. Science students’ understanding of the contribution of ecosystem functions to human well-being reinforced the importance of biodiversity education in shaping environmental concerns